2007
DOI: 10.2332/allergolint.o-06-457
|View full text |Cite
|
Sign up to set email alerts
|

Allergen-specific T-cell Response in Patients with Phenytoin Hypersensitivity; Simultaneous Analysis of Proliferation and Cytokine Production by Carboxyfluorescein Succinimidyl Ester (CFSE) Dilution Assay

Abstract: Phenytoin-specific proliferation may be detected with greater sensitivity by the CFSE dilution assay than the conventional LTT. The assay revealed that both CD4+ and CD4- T cells proliferated and produced IFN-gamma and TNF-alpha after stimulation with phenytoin. The CFSE dilution assay might be useful for the diagnosis and understanding of drug hypersensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 18 publications
2
29
0
1
Order By: Relevance
“…El estudio de Tsuge I et al 31 fue el úni-co que empleó el estudio de linfoproliferación, y halló una sensibilidad de 100% (IC95:93-100), especificidad de 91% (IC95:69-100), CP+ 11 (IC95%:2-71) e Índice J de Younden 0,91(IC95%:0,74-1,08). En la evaluación de la validez diagnós-tica de la prueba de activación de basófilos se halló una sensibilidad global de 78% (IC95%:74%-81%) con un rango de 48%-1 0 0 % .…”
Section: Resultsunclassified
“…El estudio de Tsuge I et al 31 fue el úni-co que empleó el estudio de linfoproliferación, y halló una sensibilidad de 100% (IC95:93-100), especificidad de 91% (IC95:69-100), CP+ 11 (IC95%:2-71) e Índice J de Younden 0,91(IC95%:0,74-1,08). En la evaluación de la validez diagnós-tica de la prueba de activación de basófilos se halló una sensibilidad global de 78% (IC95%:74%-81%) con un rango de 48%-1 0 0 % .…”
Section: Resultsunclassified
“…In this study, (1) the proliferation indices of T cells were assayed by CFSE-staining method with flow cytometry [32,33], which showed that the BCG HSP70 gene transfected AML/B-ALL cells significantly enhanced lymphocyte proliferation; (2) cytokine level by ELISA suggested that HSP70-transfected AML/B-ALL cells stimulated autologous T cells to secrete the highest cytokine level (IFN-γ); (3) lactate dehydrogenase (LDH) release assay used to measure killing activity of CTLs [34] showed that the killing rate of CTL in the group of HSP70-transfected AML/B-ALL cells was significantly higher than that of the wide-type AML/B-ALL cells and pDisplay-transfected ones, suggesting that BCG HSP70 gene transfection could significantly enhance the killing activity of autologous CTL on leukemia cells.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies our group has shown that the cells mainly involved at the acute phase of MPE induced by drugs were CD4+ with cytotoxic capabilities (perforin and o Without Stimulation • With Stimulation reaction, peripheral blood and the affected tissue (skin) (3,6), thus demonstrating the importance of Thl cell trafficking with effector functions between these tissues for the development of MPE. Although the involvement of CD4+ T cells and their cytokine secretion has been reported in drug allergy (22)(23), no studies have analysed the involvement of TE and TEM cells in these diseases considering also the influence of chemotactic 'cytokines and regulatory cells in the development of the disease.…”
Section: Discussionmentioning
confidence: 99%